Review on some Stefan Problems for Particle Dissolution in Solid Metallic Alloys - Vermolen, F. J.; Vuik, C.; E.; van der Zwaag, S. (Nonlinear Analysis: Modelling and Control, 2005)
This paper is a review of a suite of mathematical models of increasing complexity on particle dissolution in metallic alloys. This work deals with models for multi-component particle dissolution in multi-component alloys, where various chemical species diffuse simultaneously, and a two-dimensional model incorporating interfacial reactions as in the model of Nolfi [1]. The work is mathematically rigorous where asymptotic solutions and solution bounds are derived but is also of a practical nature as particle dissolution kinetics is modelled for industrially relevant conditions.